Improving marketing skills for salak processed products through training and mentoring for Jaya Lestari Farmers Group in Tiga Nderket Village, Karo Regency - Lita Nasution; Ahmad Afandi; Makhrani Sari Ginting; Muhammad Said Siregar; Muhammad Fitra Zambak; Rikson Asman Fertiles Siburian; Isthifa Kemal; Muhammad Thamrin; Fitria Fitria (Universitas Muhammadiyah Magelang, 2024)
The Jaya Lestari Farmers Group in Tiga Nderket Village, Karo Regency, faces challenges in improving the market competitiveness of their salak processed products due to limited knowledge and marketing skills. This community service program aimed to enhance the group's marketing capabilities through intensive training and mentoring. The program was conducted over two days at the Village Hall and involved 20 group members. Training activities covered the preparation of marketing materials, the use of information technology, and the development of social media content. Mentoring focused on integrating digital marketing strategies into the group’s business activities. Program evaluation showed significant improvements in the ability to use social media for marketing (from 30% to 85%) and in understanding marketing strategies (from 40% to 90%). This initiative successfully increased the market potential of salak processed products, expanded customer reach, and improved the welfare of group members.